The Impact of Marketing Communications on Consumer Behavior in The Saudi Arabian Telecom Industry - Manasra, Mahmoud (European Scientific Journal, ESJ, 2025)
Marketing plays a central role in helping organizations retain existing customers and attract new ones in an increasingly competitive and rapidly evolving environment. Advances in communication technologies have expanded the ability of firms to reach and engage consumers through a mix of traditional and digital channels. This study investigates how Saudi telecom operators leverage these channels to influence consumer behavior, shape perceptions, and stimulate purchasing decisions. A qualitative case study methodology was adopted, incorporating four in-depth, semi-structured interviews with marketing communication and product management specialists from major local telecom operators. These interviews provided rich, practitioner-level insights into strategic communication practices. The primary data were complemented by secondary sources, including industry reports and prior academic literature, and analyzed using thematic analysis to identify recurring patterns and to compare them with established theories of marketing communication and consumer behavior. The results show a strong and purposeful relationship between marketing communication channels and consumer behavioral responses. Telecom operators in Saudi Arabia are increasingly dependent on digital platforms - particularly social media - for targeted engagement, real-time interaction, and influencing consumer motivations at the consideration stage. Meanwhile, traditional channels such as television and outdoor advertising continue to dominate large-scale brand-building campaigns due to their broad reach and credibility. The findings further reveal that communication style, message framing, and cross-channel integration play an essential role in shaping consumer attitudes, perceptions, and intentions. Consumers’ motivations are driven primarily by utilitarian factors such as pricing, network coverage, and data speed; however, emotional and hedonic elements are strategically incorporated to reinforce brand identity and enhance customer affinity. Overall, the study underscores the critical importance of marketing communication in shaping consumer behavior within the Saudi telecom industry and highlights the deliberate strategic alignment between communication activities and desired behavioral outcomes.